61.4k views
2 votes
Solve for x and y
2 + y= -2x

-2x2+ 8xy + 42= y

User Dyesdyes
by
5.5k points

1 Answer

6 votes


\\ \sf\longmapsto 2+y=-2x---(1)


\\ \sf\longmapsto -2x^2+8xy+42=y\dots(2)

From equation (1)


\\ \sf\longmapsto y=-2x-2\dots(3)

Put in eq(2)


\\ \sf\longmapsto -2x^2+8x(-2x-2)+42=-2x-2


\\ \sf\longmapsto -2x^2-16x^2-16x+42=-2x-2


\\ \sf\longmapsto -18x^2-16x+2x+42+2=0


\\ \sf\longmapsto -18x^2-14x+44=0

On solving


\\ \sf\longmapsto x=(11)/(9)\:or\;-2

Take it whole.

  • x=-2

Put in eq(3)


\\ \sf\longmapsto y=-2(-2)-2=4-2=2

Hence

  • (x,y)=(-2,2)
User Korbes
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.